Aktualisasi Media Interaktif Berbasis Kearifan Lokal pada Pembelajaran IPS di SD Tatelek Desa Manusak - Asti Yunita Benu (Departement of Mathematics Education, 2023)
learning was carried out at Tatelek Elementary School, Manusak Village, East Kupang District, Kupang Regency. Implementation of this research aims to; 1) knowing and describing the social studies learning process at Tatelek Elementary School in Manusak Village; 2) designing interactive media based on local wisdom; and 3) actualizing interactive media based on local wisdom in social studies learning at SD Tatelek. This qualitative research is descriptive in nature involving fifth grade students as research subjects. The results of the implementation of this activity have a positive impact on each party. Teachers are more innovative and creative and more enriched in designing learning, especially social studies learning. In addition, the existence of media that is designed and provided for the school can be used as an example that adds to the teacher's insight in making and using learning media in class. Students as subjects and objects in participating in learning are also maximized. Achievement of IPS material is more effective and maximal. Based on the results of this study, it is recommended that schools and local governments design various self-development activities, especially teachers in order to improve the quality of education